Plaque erosion: a new in vivo diagnosis and a potential major shift in the management of patients with acute coronary syndromes. (9th January 2018) - Partida, Ramon A; Libby, Peter; Crea, Filippo; Jang, Ik-Kyung
Abstract: Pathology and in vivo imaging studies have identified superficial plaque erosion as a frequent and important mechanism underlying acute coronary syndromes (ACS). In contrast with plaque rupture, the pathophysiological mechanisms leading to plaque erosion remain poorly understood. The advent of intravascular imaging techniques, particularly optical coherence tomography, has aided understanding of this mode of ACS in vivo by complementing previous insights from pathology studies. Appreciation of the distinct biological and clinical mechanisms of plaque erosion points to the possibility of tailored management strategies for patients presenting with ACS.